Socio-demographic and clinico-pathological analysis of cervical cancer patients at a tertiary care centre in South-south Nigeria - Alegbeleye, Justina O.; Nyeche, Solomon; Jaja, Merry A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical cancer is a significant public health burden in low- and middle-income countries where access to screening and treatment is limited. It is the leading cause of cancer deaths in women in Africa, often due to late presentation and diagnosis. Aim of this study was to determine the socio-demographic and clinical profile of cervical cancer patients and their relationship with tumour related factors. Methods: This was a retrospective review of all cases of histologically confirmed cervical cancer patients managed at the University of Port Harcourt Teaching Hospital, Port Harcourt, over a 5-year period. A data collection form was used to obtain socio-demographic characteristics and clinical profile from the patients’ case records. Results: The mean age of the women was 53.3±8 years, with the highest prevalence in the 55-64 age group 26 (33.3%). Majority 59 (74.4%) of the women were multiparous, and 50 (64.1%) were married. Most 32 (41%) had primary education and about one-third 24 (30.8%) were farmers. The most common clinical features were vaginal bleeding, foul-smelling vaginal discharge, pelvic pain, and weight loss 46 (59%), while squamous cell carcinoma (SCC) was the predominant histological type 56 (71.8%). Only 9 (11.5%) had any form of screening for early detection of cervical cancer. Most 31 (39%) of the patients presented with stage III disease, with a median hemoglobin level of 6.8 (2.3) g/dl before treatment. About two-third 54 (69%) of them had severe anaemia. There was significant association between marital status and histological type (X2 = 42.096, p-value = 0.001). Use of oral contraceptive pills (X2 = 7.602, p-value =0.04) and menopausal state (X2 = 6828, p-value =0.05), were significantly associated with cancer stage. Conclusions: There is an urgent need to scale up advocacy for regular screening for cervical cancer and vaccination, to ensure increased awareness, early detection, and prevent the progression of early disease.